Neonatal Outcomes in Maternal Depression in Relation to Intrauterine Drug Exposure - Corti, Silvia; Pileri, Paola; Mazzocco, Martina I.; Mandò, Chiara; Moscatiello, Anna F.; Cattaneo, Dario; Cheli, Stefania; Baldelli, Sara; Pogliani, Laura; Clementi, Emilio; Cetin, Irene (Frontiers in Pediatrics, 2019)
Background SSRIs (Selective Serotonin Reuptake Inhibitors) are the most useful drugs to treat depression during pregnancy. Intrauterine exposure to SSRIs may increase the risk of growth restriction, preterm birth and neonatal complications. However, advantages in treating depression seem to exceed potential drug side effects in respect to not treated depression. SSRIs undergo extensive hepatic first-pass metabolism with the involvement of several cytochrome P450 (CYPs) enzymes. Genetic polymorphisms may influence the expression and activity of CYPs genes. The first aim of this study was to evaluate neonatal outcomes in depressed mothers exposed to SSRIs during pregnancy. SSRIs pharmacogenetics was also evaluated in a subset of mothers and fetuses. Methods In this case-control study, cases (n=43) were Caucasian women with a diagnosis of depression and/or anxiety, treated with SSRIs for the whole pregnancy. Controls (n=86) were Caucasian women without a psychiatric diagnosis and not exposed to SSRIs during pregnancy. Exclusion criteria for both groups were other psychotropic drugs, anti-epileptics, drug of abuse, alcohol addiction, maternal or fetal infectious diseases, fetal/neonatal chromosomal genetic abnormalities. Maternal and fetal blood samples were obtained at delivery to analyse genotype in 33 cases. Results The population was homogenous for demographic, anthropometric, socio-economic and obstetric variables except for smoking and mean hemoglobin values before delivery. Obstetric features, were comparable. Newborns exposed to SSRIs during fetal life were significantly more likely to be Low Birth Weight (birth weight<2500 g) (p=0.01), had significantly lower mean Apgar scores at 1’ (p=0.006) and at 5’ (p=0.023) and worse Apgar distribution at 1’ (p=0.017) and at 5’ (p=0.013). 56% of newborns presented one or more symptoms consistent with poor neonatal adaptation syndrome (PNAS). Pharmacogenetic analysis at delivery did not show significant differences in the frequencies of obstetric or neonatal complications in relation to polymorphisms. Conclusions We found that newborns exposed to SSRIs are at increased risk of poor neonatal outcomes in terms of low birth weight, low Apgar scores and, clinically, poor neonatal adaptation syndrome. Preliminary pharmacogenetic analysis showed that the degree of CYPs alterations, that depends on polymorphisms, may influence neonatal outcomes.